(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
In this note further data both on bioethology and natural biological control of Stereonychus fraxini (De Geer) (Curculionidae) are presented. The observations were carried out in some olive orchards of Western Sicily, during 2004. It was recorded that a very high percentage (85-95%) of new buds were seriously damaged by the larval actvity on the leaves. From the parasitised pupae of S. fraxini emerged the adults of several parasitoids, i. e. seven species of Chalcidoidea and one species of Braconidae, respectively. The total parasitism ranged between 59.2-72%. Calliprymna sp. and Dibracoides cionobius Graham were the most abundant chalcidoids involved.